Renewables in the Energy Transition: Evidence on Solar Home Systems and Lighting-Fuel Choice in Kenya - Jann Lay; Janosch Ondraczek; Jana Stoever (German Institute of Global and Area Studies (GIGA), 2012)
We study the determinants of households' choices of lighting fuels in Kenya, including the option of using solar home systems (SHSs). The paper adds new evidence on the factors that influence the introduction and adoption of decentralized and less carbon-intensive energy sources in developing countries. We capitalize on a unique representative survey on energy use and sources from Kenya, one of the few relatively well-established SHSs markets in the world. Our results reveal some very interesting patterns in the fuel transition in the context of lighting-fuel choices. While we find clear evidence for a crosssectional energy ladder, the income threshold for modern fuel use - including solar energy use - is very high. Income and education turn out to be key determinants of SHSs adoption, but we also find a very pronounced effect of SHSs clustering. In addition, we do not find a negative correlation between grid access and SHSs use.
Keywords: D12; O12; Q42; 330; renewable energy; household fuel choice; lighting-fuel choice; solar power use; solar home systems; Kenya; energy ladder; KIHBS; Förderung regenerativer Energien; Sonnenenergie; Energieversorgung; Energiekonsum; Privater Haushalt; Kenia